Peran Pelatihan Dan Pengembangan Profesional Dalam Meningkatkan Kompetensi Notaris - Siti Bainah, Andri Nurwandi, Istiqomah Binti Ridwan, Arya Fadilla, Ika Permata Sari, Nur Fadilah, (Pusdikra Publishing, 2024)
This study plans to decide the job of preparing and proficient improvement in working on the ability of public accountants, particularly in Asahan Regency. As we probably are aware, to understand the Republic of Indonesia as a condition of regulation based on Pancasila and the Constitution of the Republic of Indonesia 1945 to guarantee security, request and legitimate assurance for the people who need true composed proof which incorporates making sense of the conditions, occasions or lawful activities required The Office of Notary was issued in 2004 by the Law of the Republic of Indonesia Number: 30 of 2004 concerning the Notary Position as amended by Law of the Republic of Indonesia Number 2 of 2014 amended by Law of the Republic of Indonesia Number 2 of 2014 On the Amendment to the Law of the Republic of Indonesia Number 30 Year 2004 on the Position of Notary To accomplish these targets, analysts utilized information assortment methods through perception, meetings and documentation. Information that has been gotten from meetings and perceptions is handled utilizing subjective examination to decide the effect of preparing and proficient advancement in further developing public accountant ability. With this, exploration and meetings were led at one of the public accountant workplaces in Asahan Regency, in particular the Notary Office of Roy Verson Sianturi S.H., M.H. where the outcomes will be listed in discussion that will be explained below.